2021
DOI: 10.1089/hum.2019.284
|View full text |Cite
|
Sign up to set email alerts
|

Single-Use Capture Purification of Adeno-Associated Viral Gene Transfer Vectors by Membrane-Based Steric Exclusion Chromatography

Abstract: We present membrane-based steric exclusion chromatography (SXC) as a universal capture step for purification of adenoassociated virus (AAV) gene transfer vectors independent of their serotype and surface characteristics. SXC is performed by mixing an unpurified cell culture supernatant containing AAV particles with polyethylene glycol (PEG) and feeding the mixture onto a chromatography filter unit. The purified AAV particles are recovered by flushing the unit with a solution lacking PEG. SXC is an inexpensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Membrane‐based SXC was used successfully as a capture step with virtually full product recovery for both the total IAV content (aHA assay) and the HA antigen content (SRID assay) as previously reported for a similar process (Marichal‐Gallardo et al, 2017). Compared to other chromatography techniques for purification of IAV and other viruses, SXC appears to be comparable or better in terms of product recovery and ease of use, as also discussed previously (Marichal‐Gallardo et al, 2017, 2021). The ability to load and recover the product at physiological salt concentration and pH value minimizes the risk of losing biological activity compared with other techniques.…”
Section: Discussionsupporting
confidence: 59%
“…Membrane‐based SXC was used successfully as a capture step with virtually full product recovery for both the total IAV content (aHA assay) and the HA antigen content (SRID assay) as previously reported for a similar process (Marichal‐Gallardo et al, 2017). Compared to other chromatography techniques for purification of IAV and other viruses, SXC appears to be comparable or better in terms of product recovery and ease of use, as also discussed previously (Marichal‐Gallardo et al, 2017, 2021). The ability to load and recover the product at physiological salt concentration and pH value minimizes the risk of losing biological activity compared with other techniques.…”
Section: Discussionsupporting
confidence: 59%
“…The cell factor (described in Section 2.2-2) used to convert the permittivity signal to an online viable cell concentration was equal to 0.57, 0.65, and 0.44 for run 1, run 2, and the perfusion control run, respectively adenovirus (Fernandes et al, 2013;Moleirinho et al, 2020), 41% for MVA (Léon et al 2016), 52% for influenza virus , and 20%-60% for AAV production (Moleirinho et al, 2020;Terova et al, 2018) were reported. Successful application of membrane-based SXC for influenza virus, yellow fever virus, AAV, baculovirus, hepatitis C virus, and Orf virus purifications have been reported (Lothert, Offersgaard, et al, 2020;Lothert, Pagallies, et al, 2020;Lothert, Sprick, et al, 2020;Marichal-Gallardo et al, 2021;Marichal-Gallardo, 2019). This suggests that the integrated process established here may also be transferrable to other virus manufacturing processes (Bissinger et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The IAV DIPs DI244 and OP7 were produced in a cell culture-based process using a 500 mL laboratory scale stirred tank bioreactor, followed by purification and concentration by membrane-based steric exclusion chromatography [ 44 , 45 ], as described previously [ 29 , 30 ]. Production titers of 3.3 and 3.67 log hemagglutination (HA) units/100µL (quantified by the HA assay [ 46 ]) and 5.6 × 10 8 and 1.12 × 10 11 DI vRNAs/mL (quantified by real-time RT-qPCR [ 29 , 42 , 47 ]) were achieved for DI244 and OP7, respectively.…”
Section: Methodsmentioning
confidence: 99%